DESAIN EVALUASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA MODEL COUNTENANCE STAKE PADA MATA PELAJARAN IPS - Muzakir; I Wayan Widiana; I Gede Ratnaya (PGSD UNIKA SANTU PAULUS RUTENG, 2023)
Evaluation of the project to strengthen the profile of Pancasila students in social studies subjects is very important in an effort to determine the success of the program. Evaluation design is certainly needed so that it can become a reference in carrying out evaluations. One of the evaluation models used is the Countenance Stake Model. This article aims to examine the project evaluation design for strengthening the profile of Pancasila students with the Countenance Stake model. This evaluation design includes 3 aspects, namely the antecedent, transaction and outcome. The method used in this study is a literature study that uses the Stake countenance evaluation model as a reference in the evaluation design of the Pancasila profile student strengthening project. Data collection is carried out by searching literature sourced from journals, both national journals and international journals, as well as other relevant sources. The results of this study indicate that the Countenance Stake Model can be used as a design in evaluating projects to strengthen the Pancasila student profile which includes planning (antecedents), implementation (transactions) and results (outcomes).